Communities of Caring: Developing Curriculum That Engages Latino/a Students' Diverse Literacy Practices. Issue 4 (1st October 2016) - Ordoñez-Jasis, Rosario; Dunsmore, KaiLonnie; Herrera, George; Ochoa, Carlos; Diaz, Laura; Zuniga-Rios, Elizabeth
ABSTRACT: This study investigates the learning and work of a community of practice that engaged in a specific inquiry around family/community literacy and the development of a culture of caring that would connect family/community/school literacies in ways that allowed their mostly Latino/a students to develop positive student identities, enhanced personal connections to their peers, and stronger experiential responses to literacy instruction.